Elemental‐Sulfur‐Mediated Facile Synthesis of a Covalent Triazine Framework for High‐Performance Lithium–Sulfur Batteries. Issue 9 (28th January 2016) - Talapaneni, Siddulu Naidu; Hwang, Tae Hoon; Je, Sang Hyun; Buyukcakir, Onur; Choi, Jang Wook; Coskun, Ali
Abstract: A covalent triazine framework (CTF) with embedded polymeric sulfur and a high sulfur content of 62 wt % was synthesized under catalyst‐ and solvent‐free reaction conditions from 1, 4‐dicyanobenzene and elemental sulfur. Our synthetic approach introduces a new way of preparing CTFs under environmentally benign conditions by the direct utilization of elemental sulfur. The homogeneous sulfur distribution is due to the in situ formation of the framework structure, and chemical sulfur impregnation within the micropores of CTF effectively suppresses the dissolution of polysulfides into the electrolyte. Furthermore, the triazine framework facilitates electron and ion transport, which leads to a high‐performance lithium–sulfur battery. Abstract : Elemental stabilization : A covalent triazine framework (CTF) with chemically embedded polymeric sulfur (S‐CTF) was synthesized under catalyst‐ and solvent‐free reaction conditions from 1, 4‐dicyanobenzene and elemental sulfur. This material was used as a robust cathode for high‐performance lithium–sulfur batteries with very good cycling stabilities.